Counter-publics: practicalities of Malaysian media in electoral reportage / Sara Chinnasamy - Chinnasamy, Sara (2016)
This paper analyses media representations of two periods of Malaysian electoral coverage from 12th and 13th general elections. It presents arguments about some media productive interventions into deliberations about democracy in public life, through the anchoring of reformist counter-publics. The Internet’s role was recognized by scholars, activists and political analysts in driving the 2008 electoral results and turned into a political expression apparatus in the political landscape. The trends continued in 2013. Independent news portals such as Malaysiakini.com and Freemalaysiatoday.com constituted deliberative publics by mobilizing the expressive powers. This had impacted traditional media landscape, which bounded by developmental journalism. Mainstream media focuses primarily on positive stories for the benefit of the political elite illustrated in newsroom cultures, where close links between politicians, editors and publishers make it difficult for journalists to investigate political leaders. Malaysia has thus been called a fettered democracy. The grip on hegemonic power is exerted through invasive government regulation of print and broadcast media. The Internet portals became beneficiaries of an unforeseen loophole in regulation when the Internet was left free of censorship in the interests of the country’s business development. Since mainstream media and independent portals are bounded by different legal frameworks, this paper will examine in what ways their news are different and discourses of inclusion and exclusion, circulated. To understand how counter-publics work in practice, journalists’ from diverse background are interviewed through in-depth-interviews regarding their electoral experience. The findings showed that counter-publics around the independent portals are a direct result, and may explain some of the mainstream media’s ambivalence on some issues because the mere presence of independent online media increases the likelihood of diversity of opinion, and different narrativizations of reformist activities in public.